Effects of Loan Terms and Borrowers’ Behavior on Non-Performing Loans in Nigeria's Microfinance Banks - Ademola, Abimbola Oluwaseyi (Indonesian Journal Of Business And Economics, 2024)
This study investigated the effect of loan terms and borrowers' behavior on NPLs in Nigeria’s Microfinance banks. Specifically, it explored the influence of interest rates, repayment periods, loan conditions, overleveraging, loan diversion, and financial literacy, on the NPLs of 25 selected MFBs in South West Nigeria. Spearman correlation and multiple regression analyses were used to analyse the data. The results indicated that high interest rates and short repayment periods were positively linked to the increase in NPLs, meaning that borrowers have difficulties with high borrowing costs and tight repayment schedules. Moreover, rigid conditions of the loans further increased the level of NPLs due to lack of borrower flexibility. Overleveraging and loan diversion also proved to be significant enhancers of NPLs, while financial literacy turned out to reduce default risks. The study emphasizes the need to adopt flexible loan conditions and make sure clients are more financially literate, which would reduce default rates and increase sustainability for MFBs. These findings have important implications for policymakers and financial institutions concerned with enhancing the resilience of the microfinance sector in Nigeria.